2014
DOI: 10.1111/aogs.12450
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcome of unplanned out‐of‐institution births in Norway from 1999 to 2013: a cross‐sectional study

Abstract: Objective. To study the incidence, maternal characteristics and outcome of unplanned out-of-institution births (= unplanned births) in Norway. Design. Register-based cross-sectional study. Population. All births in Norway (n = 892 137) from 1999 to 2013 with gestational age ≥22 weeks. Methods. Analysis of data from the Medical Birth Registry of Norway from 1999 to 2013. Unplanned births (n = 6062) were compared with all other births (reference group). Results. The annual incidence rate of unplanned births was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
3
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 26 publications
5
42
3
3
Order By: Relevance
“…However, other studies have found no association between maternal age and the duration of the first stage [13, 34]. In our previous study of unplanned out-of-institution births in Norway, we found that older women were less likely than younger women with the same parity to have unplanned out-of-institution deliveries [5]. We then speculated that this could be due to less vigorous labor or more precautions with age, and our findings from the present study support the latter.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, other studies have found no association between maternal age and the duration of the first stage [13, 34]. In our previous study of unplanned out-of-institution births in Norway, we found that older women were less likely than younger women with the same parity to have unplanned out-of-institution deliveries [5]. We then speculated that this could be due to less vigorous labor or more precautions with age, and our findings from the present study support the latter.…”
Section: Discussionmentioning
confidence: 87%
“…We have studied unplanned out-of-institution births [5], which might occur because labor progresses faster than anticipated. A majority of the women experiencing such births are multiparous women with singleton, cephalic pregnancies in spontaneous labor at term.…”
Section: Introductionmentioning
confidence: 99%
“…However, centralization might lead to increasing numbers of unplanned out-of-hospital deliveries, as the distance to the birth unit becomes longer. This negates the positive effect of centralization, since perinatal mortality rate in unplanned out-ofhospital deliveries is shown to be at least twofold compared to hospital deliveries [12]. Also, a recent Finnish study showed that by decreasing the number of delivery units from 49 to 34, the rate of unplanned out-of-hospital deliveries doubled in two decades [8].…”
Section: Commentmentioning
confidence: 98%
“…Raziskava kaže, da se nekatere intervjuvanke, veliko bolj prvorodnice, ki so nenačrtovano rodile zunaj porodnišnice, niso zavedale pomembnosti časovne oddaljenosti in/ ali prepoznale znakov začetka poroda. Ugotovitve drugih raziskav kažejo, da je časovna oddaljenost do najbližje porodnišnice pomembno povezana z večjo pogostnostjo nenačrtovanega poroda (McLelland, et al, 2013) ter večjim deležem neonatalne mortalitete in morbiditete, ko govorimo o nenačrtovanem porodu (Scott & Esen, 2005;Blondel, et al, 2011;McLelland, et al, 2013;Gunnarsson, et al, 2014;Nguyen, et al, 2016). Čeprav je porod zunaj porodnišnice redek pojav tako pri nas kot v razvitem svetu (Blondel, et al, 2011;McLelland, et al, 2013;Gunnarsson, et al, 2014;Erlandsson, et al, 2015), je pomembno razumeti, kako ženske doživljajo takšen porod in kateri vidiki njenega doživljajskega sveta so v ospredju.…”
Section: Proces Rojevanja: Rituali Prakse In Doživljanjaunclassified
“…Ugotovitve drugih raziskav kažejo, da je časovna oddaljenost do najbližje porodnišnice pomembno povezana z večjo pogostnostjo nenačrtovanega poroda (McLelland, et al, 2013) ter večjim deležem neonatalne mortalitete in morbiditete, ko govorimo o nenačrtovanem porodu (Scott & Esen, 2005;Blondel, et al, 2011;McLelland, et al, 2013;Gunnarsson, et al, 2014;Nguyen, et al, 2016). Čeprav je porod zunaj porodnišnice redek pojav tako pri nas kot v razvitem svetu (Blondel, et al, 2011;McLelland, et al, 2013;Gunnarsson, et al, 2014;Erlandsson, et al, 2015), je pomembno razumeti, kako ženske doživljajo takšen porod in kateri vidiki njenega doživljajskega sveta so v ospredju. Porod je univerzalen dogodek, vendar pa je njegovo doživljanje zelo individualno (Lindgren & Erlandsson, 2010), kar potrjuje tudi raziskava, in se spreminja s sociopolitičnim kontekstom, v katerega je umeščen (Records & Wilson, 2011), zato je analiziranje vsakdanjega življenja in porodnih pričevanj žensk nujna in legitimna sestavina vrednosti, ki pomeni izziv »tradicionalni« vednosti, kot to imenuje Drglin (2007, p. 111).…”
Section: Proces Rojevanja: Rituali Prakse In Doživljanjaunclassified